Studies on anode mass composition and cathode flow field design for small-scale to large-scale direct methanol fuel cell stack systems - Thanarajan Kumaresan; Karthikeyan Palaniswamy; Ashley Fly; Senthilarasu Sundaram (AIP Advances, 2022)
In this research, the performance studies of a single cell Direct Methanol Fuel Cell with three different mass compositions (20%, 40%, and 60%) of platinum at anode infused in NiTiO3/C and multiple cathode flow fields, such as serpentine, parallel, and sinuous, with 25 cm2 active area. 40% platinum mass composition has been reported with a maximum power density of 24.42 mW/cm2, which is 26.8% and 10.4% higher than the performance observed in 20% and 60% platinum mass composition, respectively, on serpentine flow field. Among the various cathode flow fields, sinuous flow field provided the maximum power density of 28.69 mW/cm2, which is 17.48% and 53.83% higher in performance than that of serpentine and parallel flow fields, respectively. The best-performing catalyst mass composition and flow field, viz., 40% mass composition and sinuous flow field are scaled up to a 100 cm2 active area, and the results showed 16% lower performance compared to a 25 cm2 active area. A three-cell stack is fabricated with the best performing combination with the 100 cm2 active area that delivered a peak power output of 5.8 W, which resulted in 19.4% lower performance than 100 cm2. The stack was tested for stability for 48 h at constant voltage mode and was found that 0.002 W deviation for the entire period.